История Удмуртии, XX век: учебник для 9-го класса общеобразовательных учреждений / Т. Е. Никулина - Никулина Татьяна Евгеньевна (Удмуртия, 2011)
Экземпляры: ДО (20131014) / Инвентарный номер: 57008 / Цена: 170.00 / Авт.знак: Н 65 / ББК: 63.3(2Рос.Удм)